The Renaissance - Goodenough, Simon frey50 (New York Arco Publishing, Inc., 1981)
Presents an account of life during the Renaissance, a period which profoundly influenced the development of European civilization.
Includes bibliographical references and index
Keywords: Renaissance -- Juvenile Literature